2006
DOI: 10.1021/ja054547v
|View full text |Cite
|
Sign up to set email alerts
|

Biscyclization Reactions in Butadiyne- and Ethyne-Linked Triazenes and Diazenes:  Concerted versus Stepwise Coarctate Cyclizations

Abstract: A series of alkyne-linked bis-2H-indazoles has been prepared by the double cyclization of ethyne- or butadiyne-linked phenyltriazene or phenyldiazene moieties. Even though there are two five-membered ring cyclizations and several triple bond shifts involved, the reactions proceed rapidly under neutral conditions with mild heating, affording the heterocycles in excellent yields. DFT calculations, in agreement with experimental observations, indicate that the reactions: (1) occur via a very short-lived carbene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 47 publications
4
42
0
Order By: Relevance
“…[2,5,[7][8][9][10][11] This level of theory has proven to give reliable results that are comparable to experimental findings in prior cyclization studies. To reduce the number of conformational degrees of freedom, the NEt 2 substitution on the triazene was replaced with an NMe 2 group.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…[2,5,[7][8][9][10][11] This level of theory has proven to give reliable results that are comparable to experimental findings in prior cyclization studies. To reduce the number of conformational degrees of freedom, the NEt 2 substitution on the triazene was replaced with an NMe 2 group.…”
Section: Resultssupporting
confidence: 65%
“…[2, 7,8,10] Extension of this methodology to naphthalene derivatives would suggest three potential cycli-zation precursors 5-7, which would originate from the corresponding halonaphthalenamines 8-10 (Scheme 2). Examination of the literature revealed that related structures 9 [14] and 10 [15] are known compounds, whereas linear derivative 8 (X = I, Br) is unknown and therefore an alternate precursor is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…18 Experimental data and DFT calculations support carbene (9) as an intermediate in this stepwise, nonsynchronous coarctate reaction. Methoxy(methylthio)carbene (12) has been observed by UV photoelectron spectroscopy after gas-phase decomposition of oxadiazoline (11).…”
Section: Generationmentioning
confidence: 81%
“…More important, Austin showed that the double cyclization occurred cleanly at 90 1C in ODCB and afforded only the bisisoindazoles; cinnolines were never detected. 50 Monoyne 63 could cyclize to the corresponding bisisoindazole 64, but required higher temperatures and/or carbene stabilisers to induce cyclization (Scheme 23). 50 Interestingly, heating 61 and 63 in excess DMB or protic solvents produced only 62 and 64; as we initially hoped, carbene-trapped products were not observed.…”
Section: Even More Surprises -Butadiynyl-and Ethynyl-linked Bisdiazenmentioning
confidence: 99%
“…50 Given the high degree of reactivity of the diynyl bisdiazene, we did not even attempt to prepare the monoyne derivative.…”
Section: Even More Surprises -Butadiynyl-and Ethynyl-linked Bisdiazenmentioning
confidence: 99%